Penerapan Metode Preference Selection Index Terhadap Pemilihan Sales Terbaik - Sanriomi Sintaro (PT. Tech Cart Press, 2024)
Salesperson is an important part in a company that is responsible for selling products or services to potential customers. A salesperson's job is not only limited to selling, but also includes building strong relationships with customers, understanding their needs, and providing appropriate solutions. The best salespeople are those who have a combination of strong interpersonal skills, a deep understanding of the product or service they sell, and a dedication to providing the best service to customers. One of the main problems in choosing the best salesperson is finding a balance between technical skills and interpersonal skills. While having a solid knowledge of the products or services they sell is crucial, the ability to communicate effectively and build good relationships with customers is also crucial. The Preference Selection Index (PSI) method is an approach that allows evaluation and ranking of alternatives based on preferences relative to established criteria. The PSI method of selecting the best sales can be used to evaluate sales performance based on a number of predetermined criteria. By applying the PSI method, this study seeks to provide a more systematic and structured approach in assessing and selecting the best sales, which is expected to produce more accurate and objective recommendations. The ranking results show, for the first rank with a final PSI value of 0.912 obtained by Sales GS, the second rank with a final PSI value of 0.901 obtained by Sales HR, the third rank with a final PSI value of 0.888 obtained by Sales YP.